A corrector–predictor path-following method for second-order cone optimization. Issue 12 (1st December 2016) - Kheirfam, B.
Abstract : In this paper, we present a corrector–predictor path-following interior-point method for second-order cone optimization (SOCO) based on a new proximity measure. The algorithm produces a sequence of iterates in a neighbourhood of the central path based on a new proximity measure. We show that the algorithm is well-defined and derive the complexity bound for the algorithm. We obtain the best-known result for SOCO. The numerical results show that the proposed algorithm is effective.